1996
DOI: 10.1088/0253-6102/26/1/39
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anharmonic Vibration on the Solubility Curve of the Binary Alloy

Abstract: Taking TiCu alloy as an example, based on the measurement of thermal expansion coefficient, the harmonic vibration cpefficient and anharmonic vibration coefficient of atoms were calculated. With the help of Collins model, the author worked out the thermodynamic function and the solubility curve under the atomic anharmonic vibration. And, the influence of the anharmonic vibration was also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As brazing temperature rose above 875°C, Ti–Cu compounds dominated the seam. Due to their low CTE (about 11.15 × 10 −6 K −1 at 900°C) as well as the accommodation of TiB whiskers array, a gradient seam from ZS to TC4 was accomplished. Besides, previous studies have shown the possible role of TiB whiskers in crack deflection and loads transfer, which also attributed to the high strength of the joint.…”
Section: Resultsmentioning
confidence: 99%
“…As brazing temperature rose above 875°C, Ti–Cu compounds dominated the seam. Due to their low CTE (about 11.15 × 10 −6 K −1 at 900°C) as well as the accommodation of TiB whiskers array, a gradient seam from ZS to TC4 was accomplished. Besides, previous studies have shown the possible role of TiB whiskers in crack deflection and loads transfer, which also attributed to the high strength of the joint.…”
Section: Resultsmentioning
confidence: 99%